Dismantling the populist state : the unfinished revolution in Latin America and the Caribbean Shahid Javed Burki, Sebastian Edwards.. - Burki, Shahid Javed. (World Bank Latin American and Caribbean studies viewpoints, 1996)
"Well-written paper discusses institutional reforms needed for dismantling the populist State. Contends that such reforms, no matter how painful, must be made immediately to consolidate gains from earlier reforms"--Handbook of Latin American Studies, v. 57.